The effect of Activin A and Steroid Hormones on the Recurrent and single Abortion - Nazar Ahmed Naji; Galawesh Norri Tahrr (Tikrit Journal of Pure Science)
This study is designed to evaluate the relationship between Activin -A and the incidence of recurrent and single abortion. The study also included the Estimate of steroid hormones levels (FSH, LH and progesterone concentration through the abortion and normal pregnancy. The work performed through using 90 blood samples were taken from aborted and normal pregnant women their range ages between (15-45) years, attended Azadi teaching hospital in Kirkuk and general hospital of Kirkuk and some private medical clincs during the period from 1st of September (2012) to end of march (2013)